A Novel Third Wave Contextual Approach of Positive Behavior Support in School for Adolescent at High Psychosocial Risk: Rationale, Feasibility, and First Pilot Outcomes - Marino, Flavia (Front Psychol, 2019)
Adolescence is a stage in life when dramatic physical, cognitive and socio-emotional changes occur. When adolescents grow-up in deprived social environments, the chance of psychophysical well-being severely decreases and problems such as delinquency, substance abuse and mental health issues are much more likely to ensue. Third wave cognitive-behavioral interventions are increasingly becoming the chosen instruments to support psychological intervention for young people and adolescents. In this study, we aim to test the feasibility and the adequacy of the outcome measures of an intervention for adolescents at high psychosocial risk, using a modified Discoverer, Noticer, Advisor and Values (DNA-V) protocol aimed at increasing flexible and positive values. The project was conducted in a school located in a low Socio-Economic Status (SES) and severely deprived district of a metropolitan area in Messina, Italy, with 3 classes from 6th to 8th grade. All parents and teachers allowed participants to take part in the pilot study. However, the participants’ willingness to engage in the study was low (1 out of 3 classes). Overall, 13 adolescents (72% of the enrolled class) participated in the pilot and only 2 out of 7 teachers and no parents were available for interviews. In its current form, a full RCT is not considered feasible due to general low motivation showed by the participants. Although the sample size was small, the intervention program showed a statistically significant main effect for students’ self-report questionnaire, suggesting that those measures were appropriate. Modifications and additional measures are suggested to increase participants’ engagement and to overcome the need for parents and teachers’ interviews.